Credit Risk Management Implementation PT Bank Development Regional South & West Sulawesi - Nurfadillah, Amira; Rizal S, Muh; Muhammad Rivai, Andi (Jurnal Administrasi Bisnis, 2025)
Implementation of  Credit Risk Management of PT Regional Development Bank of South & West Sulawesi Thesis.  Business Administration Study  Program, Faculty of Social  Sciences & Law. Makassar State University. Guided by Muh. Rizal S and Andi Muhammad Rivai. P PT Regional Development Bank of South & West Sulawesi has distributed credit  to the public,  the  credit channeled by the bank  cannot be separated from non-performing loans that can harm the  bank.   This study aims to determine the application of credit risk management in reducing non-performing loans at Bank Sulselbar. The type of research used in this thesis is a  qualitative discriptive method. The  data in this study were obtained from primary data and secondary data.  The data collection techniques used were observation, interviews and documentation. The results  of  this study show that: (1) The application of risk management in  resolving non-performing loans can be done in 3 (Three) stages, namely Rescheduling, Reconditioning, and Restructuring.  The Bank will carry out credit rescue in an effort to reduce losses carried out by means of Restructuring, namely (Rescheduling, Reconditioning and Restructuring). This restructuring is carried out if the customer's business is in good condition in terms of installment payments. (2) The determinants that influence risk management in its application are supporting factors consisting of the pillars of risk management implementation. The first is active supervision by the Board of Commissioners and Board of Directors. Second, the adequacy of policies, procedures and limit setting. Third, the adequacy of the process of identification, measurement, monitoring and control of risks. Fourth, a comprehensive internal control system. Meanwhile, the inhibiting factor is due to differences of opinion in the identification  of credit distribution between divisions in the credit sector so that friction occurs, then there is  amutasi system  so that there are some human resources who still lack knowledge about risk management.  Keywords: Risk Management, Non-performing loans, Bank